HUBUNGAN PENGETAHUAN, SIKAP, DAN TINDAKAN LANSIA DENGAN STATUS KEBERSIHAN GIGI DAN MULUT (Tinjauan pada Panti Sosial Tresna Werdha di Kalimantan Selatan) - Patrycia Solavide Br. Sijabat; Isnur Hatta; Galuh Dwinta Sari (Universitas Lambung Mangkurat, 2020)
ABSTRACTBackground: The elders naturally have a decrease in their ability to regenerate and impacted on the health of their dental and oral. The behavior of maintaining oral hygiene is one that plays a role in maintaining the health of the elderly's body. Purpose: To analyze the relationship between knowledge, attitudes and actions of elderly with dental and oral hygiene status at the nursing home in South Kalimantan. Methods: This study was an analytic observational study with a cross sectional design, conducted on 32 elders at the nursing home in South Kalimantan. Each respondent was examined with OHIS index then answered the questionnaire. Data analysis used the Spearman correlation test. Results: The Spearman correlation test showed a relationship between knowledge and actions of elders with dental and oral hygiene status (p <0.05) and there was no significant relationship between elders’s attitudes with oral and dental hygiene status at nursing home in South Kalimantan (p > 0.05). Conclusion: There was a significant relationship between knowledge and actions of the elders with the status of oral hygiene and there was no significant relationship between the attitude of the elders and the status of oral hygiene at the nursing home in South Kalimantan. Keywords: Attitude, Action, Elderly, OHIS, Knowledge ABSTRAKLatar Belakang: Lanjut usia secara alami mengalami penurunan kemampuan regenerasi dan berdampak pada kesehatan rongga mulutnya. Perilaku pemeliharaan kebersihan mulut merupakan salah satu yang berperan dalam menjaga kesehatan tubuh lansia. Tujuan: Menganalisis hubungan pengetahuan, sikap dan tindakan lansia dengan status kebersihan gigi dan mulut di Panti Sosial Tresna Werdha di Kalimantan Selatan. Metode: Penelitian ini merupakan penelitian observasional analitik dengan rancangan cross sectional, dilakukan pada 32 lansia pada Panti Sosial Tresna Werdha di Kalimantan Selatan. Masing-masing responden dilakukan pemeriksaan dengan indeks OHIS kemudian menjawab pertanyaan pada kuesioner. Analisis data menggunakan uji korelasi Spearman. Hasil Penelitian: Uji korelasi spearman menunjukkan hubungan bermakana pengetahuan dan tindakan lansia dengan status kebersihan gigi dan mulut (p<0,05) serta tidak terdapat hubungan bermakna antara sikap lansia dengan status kebersihan gigi dan mulut di Panti Sosial Tresna Werdha di Kalimantan Selatan (p>0,05). Kesimpulan: Terdapat hubungan bermakna antara pengetahuan dan tindakan lansia dengan dengan status kebersihan gigi dan mulut serta tidak terdapat hubungan bermakna antara sikap lansia dengan status kebersihan gigi dan mulut di Panti Sosial Tresna Werdha di Kalimantan Selatan. Kata kunci: Lansia, OHIS, Pengetahuan, Sikap, Tindakan,